Little you ebook - Van Camp, Richard (2013)
"You are life and breath adored. You are us and so much more..." Richard Van Camp, internationally renowned storyteller and bestselling author of the hugely successful Welcome Song for Baby: A Lullaby for Newborns, has partnered with award-winning illustrator Julie Flett to create a tender board book for babies and toddlers that celebrates the potential of every child. With its delightful contemporary illustrations, Little You is perfect to be shared, read or sung to all the little people in your life—and the new little ones on the way! Available in French as Tout petit toi and in Spanish as Tú eres tú.